2020
DOI: 10.1093/jscr/rjaa099
|View full text |Cite
|
Sign up to set email alerts
|

An incarcerated Spigelian hernia with the appendix in the sac passing though all layers of the abdominal wall: an unusual cause for chronic right iliac fossa pain

Abstract: Abdominal wall hernias are a common pathology and source of morbidity including chronic pain. They occur in various anatomical areas; amongst the rarest locations is the Spigelian hernia accounting for <2% of all abdominal hernias. We present a case report of a patient with chronic right iliac fossa pain caused by an incarcerated Spigelian hernia containing her appendix within the hernial defect. Rarer still is that her hernial defect penetrated all three layers of anterior abdominal wall, typically a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…However, this study showed no significant differences in readmission or reoperation rates in patients undergoing emergency hernia repair, compared to elective. This finding is in contrast to recommendations from low volume publications and case reports showing that a Spigelian hernia is associated with a high risk of incarceration and therefore recommends elective repair for all patients with Spigelian hernias [5][6][7].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…However, this study showed no significant differences in readmission or reoperation rates in patients undergoing emergency hernia repair, compared to elective. This finding is in contrast to recommendations from low volume publications and case reports showing that a Spigelian hernia is associated with a high risk of incarceration and therefore recommends elective repair for all patients with Spigelian hernias [5][6][7].…”
Section: Discussioncontrasting
confidence: 92%
“…The diagnosis is therefore often first suspected when symptoms occur [4]. The defect of a Spigelian hernia is usually small and with sharp fascial margins, and risk of incarceration is described in the literature [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple intra-abdominal organs have been reported to have been found in the SH as large bowel, stomach, gallbladder, Meckel diverticulum, ovary, testis, leiomyoma of the uterus, and even bladder [1]. The involvement of appendix has also been described in various case reports [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (table 1).…”
Section: Epidemiologymentioning
confidence: 99%
“…Martín-Mattar [5] 2020 Necrotic appendicitis Transverse incision: appendectomy and hernioplasty with suture of aponeurosis of the external oblique muscle and sublay mesh placement of Prolene® Page [6] 2020 None Conservative management for patient's preference Sobrado [7] 2020 Intraparietal appendix in previous liver transplantation Open appendectomy and hernia repair with polypropylene mesh below the external oblique fascia Anand [8] 2020 Necrotic and perforated appendix with surrounding purulence Exploratory laparotomy revealing the distal end of the appendix going through the abdominal defect into the hernial sac. Due to the difficulty in grasping, a counterincision was made over the area of the defect.…”
Section: Author Year Intraoperative Finding Treatmentmentioning
confidence: 99%